Kemampuan Berpikir Kreatif dalam Pembelajaran Matematika berdasarkan Aspek Munandar - Siti Ulpatun Nadhiroh (Journal of Education and Teaching (JET), 2023)
The ability to think creatively is an ability that must be mastered to find new ideas that are different from those that already existed before. This study aims to determine the existence of students' creative thinking skills in learning mathematics based on Munandar aspects. Using exploratory research procedures with a systematic literature review research model by analyzing a sample of 16 scientific articles downloaded from Google Scholar. These articles discuss creative thinking skills based on Munandar aspects, namely fluency, flexibility, originality, elaboration. From some of the data excavated, the results of the research on students' creative thinking skills based on the Munandar aspect showed that junior high and high school students were higher in the fluency aspect and obtained a percentage of 29% of all aspects with an average of 56. While the flexibility and elaboration aspects obtained a percentage 24% of all aspects with an average of 46.5. In the aspect of authenticity, it obtained a percentage of 23% of all aspects with an average percentage of 44.5.